2004
DOI: 10.1177/0310057x0403200203
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Use of Herbal Medicines and Vitamin Supplements

Abstract: There has been a definite increase in the popularity and use of complementary and alternative medicines, including herbal medicines, in the last ten years. The aim of this study was to determine the prevalence and patterns of use of herbal medicines and vitamin supplements by patients in the preoperative period. A questionnaire was offered to all patients attending the pre-admission clinics at St. Vincent's Hospital and Box Hill Hospital, Melbourne, over an eight-month period in 2002. In all, 1102 questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
(72 reference statements)
2
11
1
Order By: Relevance
“…As a result, perioperative CM use is not identified by most surgeons, anaesthetists and pharmacists and therefore products with the potential to induce adverse outcomes or drug interactions are unmanaged placing patients at risk. Complementary medicine usage detected in this study population was greater than previously reported in another Australian study of surgical patients and disclosure was worse with 56% of patients not telling any hospital staff about their use [20]. In comparison to a survey of people with cardiovascular disease in the United States, our study population had greater use of fish oil supplements (25% compared to 12%) and substantially less use of the herbal medicines echinacea (3% vs 34%), garlic (1% vs 23%), ginseng (0% vs 22%) and ginkgo biloba (3% vs 22%) suggesting a cultural difference in usage patterns [21].…”
Section: Therapies Into Their Healthcare Cardiothoracic Surgical Patcontrasting
confidence: 76%
See 2 more Smart Citations
“…As a result, perioperative CM use is not identified by most surgeons, anaesthetists and pharmacists and therefore products with the potential to induce adverse outcomes or drug interactions are unmanaged placing patients at risk. Complementary medicine usage detected in this study population was greater than previously reported in another Australian study of surgical patients and disclosure was worse with 56% of patients not telling any hospital staff about their use [20]. In comparison to a survey of people with cardiovascular disease in the United States, our study population had greater use of fish oil supplements (25% compared to 12%) and substantially less use of the herbal medicines echinacea (3% vs 34%), garlic (1% vs 23%), ginseng (0% vs 22%) and ginkgo biloba (3% vs 22%) suggesting a cultural difference in usage patterns [21].…”
Section: Therapies Into Their Healthcare Cardiothoracic Surgical Patcontrasting
confidence: 76%
“…Consistent with findings from studies of general surgical patients, there is little discussion about CMs between hospital medical staff and cardiac surgery patients [17,18,20]. This study extends the literature on patient disclosure and suggests that patients do not tell hospital staff about their use of CMs primarily because they are not asked or do not think it is important and not because they fear a negative response.…”
Section: Communicationsupporting
confidence: 73%
See 1 more Smart Citation
“…Compared to non-European countries, one study from China [19] reported higher prevalence, while five studies from the USA [10, 11, 13, 16, 20] and two from Canada [15, 21] reported lower prevalence. In a study carried out in USA [12], 12.9% of middle-aged and older cardiac patients confirmed vitamin use, 11.6% herbs and folk remedies use, and 3.6% use of homeopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest prevalence was reported in a survey conducted in a UK hospital setting [14] on 2723 patients: 4.8% of them took one or more herbal medications. Other surveys were conducted in USA [913, 16, 20], in Europe [17, 18], and Canada [15, 21]. To our knowledge, no studies on adult patients in preoperative period have been conducted in Italy.…”
Section: Introductionmentioning
confidence: 99%